Mitogen-activated protein kinase signaling pathways promote low-density lipoprotein receptor-related protein 1-mediated internalization of beta-amyloid protein in primary cortical neurons. (July 2015) - Yang, Wei-Na; Ma, Kai-Ge; Qian, Yi-Hua; Zhang, Jian-Shui; Feng, Gai-Feng; Shi, Li-Li; Zhang, Zhi-Chao; Liu, Zhao-Hui
Highlights: Aβ1–42 oligomers could be internalized into endosomes/lysosomes and mitochondria. LRP1 increased Aβ1–42 internalization in cortical neurons. Activation of p38 MAPK and ERK1/2 resulted in Aβ1–42 internalization. MAPK signaling pathways regulated LRP1-mediated Aβ1–42 internalization. Abstract: Mounting evidence suggests that the pathological hallmarks of Alzheimer's disease (AD) are caused by the intraneuronal accumulation of beta-amyloid protein (Aβ). Reuptake of extracellular Aβ is believed to contribute significantly to the intraneuronal Aβ pool in the early stages of AD. Published reports have claimed that the low-density lipoprotein receptor-related protein 1 (LRP1) mediates Aβ1–42 uptake and lysosomal trafficking in GT1–7 neuronal cells and mouse embryonic fibroblast non-neuronal cells. However, there is no direct evidence supporting the role of LRP1 in Aβ internalization in primary neurons. Our recent study indicated that p38 MAPK and ERK1/2 signaling pathways are involved in regulating α7 nicotinic acetylcholine receptor (α7nAChR)-mediated Aβ1–42 uptake in SH-SY5Y cells. This study was designed to explore the regulation of MAPK signaling pathways on LRP1-mediated Aβ internalization in neurons. We found that extracellular Aβ1–42 oligomers could be internalized into endosomes/lysosomes and mitochondria in cortical neurons. Aβ1–42 and LRP1 were also found co-localized in neurons during Aβ1–42 internalization, and they could form Aβ1–42 –LRP1 complex. Knockdown of LRP1 expression significantly decreased neuronal Aβ1–42 internalization. Finally, we identified that p38 MAPK and ERK1/2 signaling pathways regulated the internalization of Aβ1–42 via LRP1. Therefore, these results demonstrated that LRP1, p38 MAPK and ERK1/2 mediated the internalization of Aβ1–42 in neurons and provided evidence that blockade of LRP1 or inhibitions of MAPK signaling pathways might be a potential approach to lowering brain Aβ levels and served a potential therapeutic target for AD.